Tropiorhynchus annandalei (Coleoptera: Scarabaeidae: Rutelinae), a new species from Maharashtra, India - Gupta, Devanshu; Chandra, Kailash (Zootaxa, 2017)
Tropiorhynchus annandalei new species (Coleoptera: Scarabaeidae: Rutelinae: Anomalini: Anisopliina) from Bhimshankar Wildlife Sanctuary, Pune district, Maharashtra State, India is described, diagnosed, and illustrated. The new species is compared with all its congeners: Tropiorhynchus orientis (Newman, 1838), T. podagricus (Burmeister, 1844), and T. umbrinus Machatschke, 1954. The newly described species differs from all its congeners by the unique structure of aedeagus, sculpturing of pronotum, medially smooth pygidial surface, and elytral markings. An illustrated key to the species of the genus Tropiorhynchus Blanchard, 1851 is also provided.